2021
DOI: 10.1111/jfpp.15216
|View full text |Cite
|
Sign up to set email alerts
|

Black pepper essential oil nanoemulsions formulation using EPI and PIT methods

Abstract: In this study, black pepper essential oil nanoemulsions formulated using low-energy methods (emulsion phase inversion and phase inversion temperature) were compared. In both the methods, optimum components' concentration was 10% of essential oil, 20% of Tween 80, and 70% of distilled water. All nanoemulsions were unchanged after centrifuging at 825 or 1,467 g for 10 min and were more stable when kept at 30°C. Phase inversion temperature nanoemulsions quickly increased droplet size and polydispersity index afte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(5 citation statements)
references
References 44 publications
0
5
0
Order By: Relevance
“…The study showed that the sous vide method with the combination of EOs is an effective method and it can be used to protect the microbiota of turkey meat and L. monocytogenes survival. According to Hien and Dao (2021), while EOs are used and added to food products, they are not very effective in their pure form. They attributed the reason for the lower effectiveness of the pure oils to the lipophilic nature of the oils and the difficulties caused by this when used in food products.…”
Section: Antimicrobial Activitymentioning
confidence: 99%
“…The study showed that the sous vide method with the combination of EOs is an effective method and it can be used to protect the microbiota of turkey meat and L. monocytogenes survival. According to Hien and Dao (2021), while EOs are used and added to food products, they are not very effective in their pure form. They attributed the reason for the lower effectiveness of the pure oils to the lipophilic nature of the oils and the difficulties caused by this when used in food products.…”
Section: Antimicrobial Activitymentioning
confidence: 99%
“…Food grade nano-emulsions have been widely used to enhance the water solubility and stability of essential oils [73]. The cellulose nanofibrils films prepared by O/W Pickering emulsion with oregano essential oil exhibit excellent antioxidant activity [74].…”
Section: Essential Oil As Antioxidant Agentmentioning
confidence: 99%
“…Turbidity was calculated after determining the optical density absorbance of the emulsion using a spectrophotometer MRC Spectro V--11D at 600 nm. The turbidity was obtained using the following equation 2 (Hien and Dao, 2021):…”
Section: Emulsion Characterizationmentioning
confidence: 99%